A Case Report of Steroid-Resistant Cryptogenic Organizing Pneumonia Managed with Intravenous Immunoglobulins - Christian Akem Dimala; Urvi Patel; Benjamin Lloyd; Anthony Donato; William B. Kimmel; Robert Hallowell; Caitlyn Moss (Case Reports in Pulmonology)
Fewer than ten reported cases of cryptogenic organizing pneumonia (COP) have been managed with intravenous immunoglobulins (IVIg). We report a case of a 72-year-old man who presented with a worsening cough and diffuse opacities on chest radiograph. Following no improvement with antibiotics and negative complementary investigations for infectious, malignant, and autoimmune etiologies, COP was confirmed on lung biopsy. Due to continued clinical deterioration despite high-dose steroids and new severe steroid-induced hallucinations, the patient was placed on intravenous immunoglobulins (IVIg) and mycophenolate mofetil and made a satisfactory recovery. IVIg should be considered as an important steroid-sparing alternative in patients with COP.